Diseño de una plataforma de movimiento con tres grados de libertad para los simuladores de la Corporación de Alta Tecnología para la Defensa (2020)
This research paper describes the development of the degree project presented at the Corporación de Alta Tecnología para la Defensa (CODALTEC), where the design of a motion platform with three degrees of the freedom for the simulators of the corporation is carried out, thus continuing with the second stage of it is line of investigation. In the methodology used for development of this project, are stared the requirements and mathematical theoretical foundations necessary to star the modeling stage of each of the components of the motion platform using computational tools for the development of mathematical calculations and assisted design by computer CAD in order to obtain the necessary information and documentation for its subsequent manufacturing process and achieve the objective of mechanical design, leaving the basis for future research as a control system , integration with simulation engines, among others that can complement this project.